Goat-derived cell line (Capra hircus) TCh generated by karyological and morphological transformation of YаDK-04 CCL during subcultivation with lanthanide-treated bovine serum - E. A. Trofimova; S. V. Kononova; I. N. Shumilova; B. L. Manin (Ветеринария сегодня)
Ability of the continuous cell lines to evolve enables generation of new transformed cell cultures with unlimited life potential and diﬀerent from the original prototypes in the process of sequential cultivation. There are practically no universal mechanisms and methods for new cell line generation. But it was noted that cell immortalization is associated with chromosomal rearrangements (chromatid morphology) and changes in the number of chromosomes. The paper presents the results of the generation of a new Testis Capra hircus(TCh) cell line, suitable for eﬀective replication of dermatotropic and other types of animal viruses, in order to scale up viral material used for the manufacture of the means for animal disease speciﬁc prevention and diagnosis. The monolayer TCh cell line was transformed from the continuous YаDK-04 cell line as a result of more than 50 passages in the growth medium supplemented with 10% of lanthanide-treated bovine serum. Use of the bovine serum puriﬁed and supplemented with lanthanides during the cultivation of the continuous cell line YаDK-04 led to signiﬁcant chromosomal rearrangements and contributed to the formation of a stable and productive new TCh cell line, which diﬀered in cytomorphological and karyological characteristics and had unlimited potential for passaging without changing the cell karyotype and morphology. The novel continuous cell line proved to be suitable for eﬀective reproduction of such disease pathogens as lumpy skin disease, sheep pox, peste des petits ruminants agents. These are mainly viruses of dermatotropic origin.